Westonci.ca is the premier destination for reliable answers to your questions, provided by a community of experts. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
- two solutions
x = 1, 3
Explanation:
[tex]\sf f(x)=x^2-4x+3[/tex]
[tex]\rightarrow \sf x^2-4x+3=0[/tex]
[tex]\rightarrow \sf x^2-3x-x+3=0[/tex]
[tex]\rightarrow \sf x(x-3)-1(x-3)=0[/tex]
[tex]\rightarrow \sf (x-1)(x-3)=0[/tex]
[tex]\rightarrow \sf x-1=0, \ x-3=0[/tex]
[tex]\rightarrow \sf x=1, \ x=3[/tex]
Thus, there are two solutions and the values are 1 and 3
Let's see
[tex]\\ \rm\rightarrowtail f(x)=0[/tex]
[tex]\\ \rm\rightarrowtail x^2-4x+3=0[/tex]
[tex]\\ \rm\rightarrowtail x^2-3x-x+3=0[/tex]
[tex]\\ \rm\rightarrowtail x(x-3)-1(x-3)=0[/tex]
[tex]\\ \rm\rightarrowtail (x-1)(x-3)=0[/tex]
[tex]\\ \rm\rightarrowtail x=1,3[/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.